Potential Classification Criteria for Rheumatoid Arthritis After Two Years: Results From a French Multicenter Cohort. Issue 8 (26th July 2013) - Saraux, Alain; Tobón, Gabriel J.; Benhamou, Mathilde; Devauchelle‐Pensec, Valérie; Dougados, Maxime; Mariette, Xavier; Berenbaum, Francis; Chiocchia, Gilles; Rat, Anne‐Christine; Schaeverbeke, Thierry; Rincheval, Nathalie; Meyer, Olivier; et al.
<x xml:space="preserve">Abstract</x> Objective To determine agreement among the 2010 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) criteria, a diagnosis of rheumatoid arthritis (RA) by a rheumatologist, and other criteria previously used to classify arthritis. Methods We used a nationwide longitudinal prospective cohort of patients with recent‐onset arthritis. After 2 years, the patients were classified as receiving disease‐modifying antirheumatic drugs (DMARDs), having synovitis, having joint erosions typical of RA, having a rheumatologist diagnosis of RA with >50.0% certainty, having a no better alternative diagnosis with >50.0% certainty, and having a diagnosis of RA using the 1987 ACR criteria and the 2010 ACR/EULAR criteria. Agreement among these criteria was assessed based on Cohen's kappa coefficient, where ≥0.80 = excellent, 0.60–0.79 = good, 0.40–0.59 = moderate, and <0.40 = poor. Results Of the 692 evaluated patients, 544 (78.6%) had persistent arthritis (defined as synovitis, ongoing DMARD treatment, or both) after 2 years. Among these 544 patients, 496 (91.2%) were receiving DMARDs. Agreement among all criteria was poor (estimated κ = 0.09–0.43), except when including a rheumatologist diagnosis of RA with >50.0% certainty or a no better alternative diagnosis with >50.0% certainty (estimated κ = 0.69–0.81). The strongest associations with a rheumatologist diagnosis of RA with >50.0% certainty were the 2010 ACR/EULAR criteria and the combination of no better alternative diagnosis, persistent arthritis, 1987 ACR criteria, and positive anti–citrullinated protein antibody. Conclusion Rheumatologist diagnosis of RA with >50.0% certainty after 2 years agreed well with the 2010 ACR/EULAR criteria or a combination of items including no better alternative diagnosis, confirming high value as classification criteria after 2 years of followup.